Novel therapeutic targets in salivary duct carcinoma uncovered by comprehensive molecular profiling. (14th October 2019) - Gargano, Stacey M.; Senarathne, Wijendra; Feldman, Rebecca; Florento, Elena; Stafford, Phillip; Swensen, Jeffrey; Vranic, Semir; Gatalica, Zoran
Abstract: Salivary duct carcinoma (SDC) is a rare, aggressive salivary gland malignancy, which often presents at an advanced stage. A proportion of SDC are characterized by HER2 amplification and/or overexpression of androgen receptor (AR), which could be targeted in a subset of patients, but the presence of AR splice variant‐7 (AR‐V7) in some SDC cases could result in resistance to anti‐androgen therapy. We evaluated a cohort of 28 cases of SDC for potentially targetable biomarkers and pathways using immunohistochemistry (IHC) and next‐generation sequencing (DNA and RNA) assays. Pathogenic genetic aberrations were found in all but 1 case and affected TP53 (n = 19), HRAS (n = 7), PIK3CA, ERBB2 (HER2), and NF1 (n = 5 each); KMT2C (MLL3) and PTEN (n = 3 each); BRAF (p.V600E), KDM5C and NOTCH1 (n = 2 each). Androgen receptor was expressed in all cases and 13 of 27 harbored the AR‐V7 splice variant (including a case without any other detectable genetic alteration). HER2 IHC was expressed in 11 of 28 cases. The majority of SDC cases had no biomarkers predictive of immunotherapy response: 5 cases exhibited low (1%‐8%) programmed death ligand 1 (PD‐L1) expression in tumor cells, 2 cases exhibited elevated TMB, and no samples exhibited microsatellite instability. Notably, the pre‐treatment biopsies from 2 patients with metastatic disease, who demonstrated clinical responses to anti‐androgen therapy, showed AR expression and no AR splice variants. We conclude that comprehensive molecular profiling of SDCs can guide the selection of patients for targeted therapies involving AR, HER2, PD‐L1, mitogen‐activated protein kinase, and PIK3CA pathways. Abstract : Salivary duct carcinoma (SDC) is a genetically diverse malignancy associated with several potentially targetable molecular pathways that have been uncovered by comprehensive molecular profiling. Our study detected genetic aberrations in 27 of 28 cases of SDC, including targetable alterations involving PIK3CA/PTEN, BRAF, and HER2. In addition, androgen receptor splice variant AR‐V7 was found in approximately half of cases, which has implications in resistance to anti‐androgen therapy.